Energy-efficient connected-coverage in wireless sensor networks. (2nd June 2008) - Cardei, Ionut; Cardei, Mihaela
This paper addresses the target coverage problem inWireless Sensor Networks (WSNs). Communication and sensing consume energy, therefore, efficient power management can extend network lifetime. In this paper, we consider a large number of sensors randomly deployed to monitor a number of targets. Each target may be redundantly covered by multiple sensors. To conserve energy, we organise sensors in sets activated sucessively. In this paper, we introduce the Connected Set Covers (CSC) problem that has as objective finding a maximum number of set covers such that each sensor node to be activated is connected to the Base Station (BS). A sensor can participate in multiple sensor sets, but the total energy spent in all sets is constrained by the initial energy reserves. We show that the CSC problem is NP-complete and we propose three solutions: an Integer Programming (IP)-based solution, a greedy approach and a distributed and localised heuristic. Simulation results that validate our approaches are also presented.